A Histological method for the Biological estimation of Vitamin A - Coetzee, W H K (Division of Physiological Sciences, 2020)
There are considerable differences between physico-chemical and biological results of Vitamin A estimations, owing to the fact that "the analyst determines the proportion of a substance present, whilst the bioassayist determines the effect"